Female Inmates: Coping with Imprisonment and Separation from Family and Friends - Celinska, Katarzyna (Women & criminal justice, 2022)
In this study coping with imprisonment among female inmates, and how it relates to experiencing separation from family and friends, is being explored. Data was collected via a survey of 194 female inmates in a Northeastern state correctional facility for women. The self-reported data included the Brief COPE assessment, as well as demographic and “contact” variables: visits, phone calls, and letter writing. The findings indicate that female prisoners tend to utilize adaptive coping methods to deal with their imprisonment. Specifically, letter writing was found to be positively associated with adaptive coping. However, visits from family members and from children were correlated with maladaptive coping and contributed to explaining the Negative Coping Index. Based on the results of descriptive and multivariate analyses, the correctional policies are suggested to better assist female prisoners’ cope with their imprisonment.